En farmakokinetisk pilotstudie av olika beredningar av bensylpenicillin intramuskulärt till häst - Lindberg, Julia (2009)
Penicillin G (benzylpenicillin) is the most commonly used antimicrobial substance used in equine medicine today. Two forms of penicillin G are available for equine use; one form is the poorly soluble penicillin G procaine and the other is the very soluble sodium salt. Although penicillin has a wide safety margin and is considered to possess a good tolerance, reactions due to side effects are sometimes encountered, which commonly is named "penicillin-shock". The etiology behind penicillin shock in horses is not completely understood, but the most common reason is believed to be procaine toxicity. In order to avoid the risk of toxic reactions against procaine, penicillin G sodium can be used. In the literature contradictory information on the possibility of the usage of penicillin G sodium intramuscularly have been found. It is therefore essential to investigate the pharmacokinetics for penicillin G sodium following intramuscular injection in horse. The aim of the present study was to examine the pharmacokinetics of penicillin G following intramuscular administration of penicillin G sodium and penicillin G procaine, respectively.